Assessment of the quality of water resources for drinking, agriculture and industry in karstic aquifer of Roein Esfarayen basin of North khorasan province - Mohammad Motamedi Rad; Leila Goli Mokhtari; Shahram Bahrami; Mohammad ali zanganeh asadi (تحقیقات کاربردی علوم جغرافیایی)
Groundwater resources are important part of the sweet water available to humans. The present study studies and evaluates the quality of water resources of karstic basin of Roein Esfarayen. For this purpose, sampling of water from water sources was carried out and groundwater quality of the area was evaluated in terms of drinking, agriculture and industry using Schoeller, Wilcox and Langelier diagrams, Water Quality Index( WQI) and groundwater quality index (GQI). According to the results of the analysis of the samples taken and the relevant charter diagrams, most of the water sources in the area were in the good category for drinking. The results of the Wilcox diagram showed that only S7 (Springs of Zargara), S6 (Springs of Sarang Zwucha) and S20 samples (rivers at the basin outlet) had saline water but could be used for agriculture and the rest were suitable for agriculture. The water quality table of the region's springs in terms of industrial use also showed that all of the water samples of the region except the Springs of Sangvah, which contains sediment-bearing water, have corrosive properties. The WQI index is also indicative of the quality of all samples taken in drinking water, and only the surface water of the basin outlet whose WQI is above 50 is in good condition. Location and quality zoning of drinking water from the GQI index was also carried out. The GQI quality index in the region varied from 93.42 to 95.87 in the region. Therefore, it can be said that although the minimum quality of samples is related to surface water of the basin, but this quality value is also in the appropriate quality category. Therefore, in total, all the water resources of the study area are in the category of quality in terms of drinking water standards